An Analysis of Moral Values in the Film ‘Titip Surat untuk Tuhan’ by Karsono Hadi - Suryani, Lilis; Malik, Abdul; Dwi Leoni, Tessa; Elfitra, Legi; Suhardi; Zaitun (Raja Zulkarnain Education Foundation, 2025)
Kata Kunci: Analisis, Nilai Moral, Film Titip Surat untuk Tuhan Penelitian ini bertujuan untuk mendeskripsikan nilai moral yang terdapat dalam film Titip Surat untuk Tuhan. Metode yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan kualitatif. Data dalam penelitian ini berupa kata-kata atau kalimat dari film Titip Surat untuk Tuhan karya Karsono Hadi dan sumber data adalah film. The film Titip Surat untuk Tuhan told the story of a simple family tested when the eldest child falls ill with a serious illness. To that end, his younger sibling writes a letter to God, hoping for his brother's recovery. That's a snippet from the film Titip Surat untuk Tuhan. This study aims to describe the moral values contained in the film Titip Surat untuk Tuhan. The method used in this study is a descriptive qualitative approach. This research took place in the even semester of the 2024/2025 academic year. The data in this study are words or sentences from the film Titip Surat untuk Tuhan by Karsono Hadi. The research instrument is the researcher himself. The data collection techniques in this study are listening and note-taking techniques using time and tool triangulation validation. The data analysis technique for moral values contained in the film Titip Surat untuk Tuhan in this study was carried out by reducing, presenting, and drawing conclusions from the data. The results of the study show that the moral values in this film include: (1) moral values related to oneself, namely patience, never giving up, humility, honesty, and responsibility; (2) moral values related to other humans or the surrounding environment, namely friendship, family, and love; (3) moral values related to God, namely worship. This film displays moral values ??emotionally and touchingly, and provides examples of positive attitudes to the audience.